Medical sciences at a glance - Randall, Michael D. (At a glance series (Oxford, England), 2014)
The definitive companion for medical science study and revision Medical Sciences at a Glance consolidates the scientific knowledge a student needs to know to provide a solid framework of key facts to build on. Concise, easy to follow, written specifically for medical students, and using the unique at a Glance style to convey key concepts, Medical Sciences at a Glance also demonstrates vital links between different topics and across systems. It is the perfect resource for bridging the gap between A-Level and university, studying a new topic, revising for exa